2009
DOI: 10.1586/14787210.7.1.37
|View full text |Cite
|
Sign up to set email alerts
|

Prospects for the control of neglected tropical diseases by mass drug administration

Abstract: The prospects for the control of neglected tropical diseases, including soil-transmitted helminthiasis, shistosomiasis, lymphatic filariasis, onchocerciasis and trachoma, through mass drug administration, are exemplified by the elimination of the trachoma as a public-health problem in Morocco. In spite of this and other striking successes, mass drug administration programs are faced with major challenges resulting from suboptimal coverage and lack of efficacy. At current suboptimal coverage rates, programs may… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
66
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(68 citation statements)
references
References 192 publications
1
66
0
1
Order By: Relevance
“…This is similar to works carried out by [15][16][17]19,20]. The study also revealed two cases of multiple or poly-parasitism of which Hookworm and Trichuris occurred in both.…”
Section: Discussionsupporting
confidence: 91%
“…This is similar to works carried out by [15][16][17]19,20]. The study also revealed two cases of multiple or poly-parasitism of which Hookworm and Trichuris occurred in both.…”
Section: Discussionsupporting
confidence: 91%
“…The control or elimination of the 'tool ready' neglected tropical diseases (NTDs) onchocerciasis, lymphatic filariasis (LF), soil transmitted helminthiasis (STH) and schistosomiasis has been a topic of renewed interest in recent years since all may be controlled or eliminated by mass drug administration (MDA) of safe and effective medicines, many of which are donated by large pharmaceutical companies (Brady et al, 2006;Musgrove and Hotez, 2009;Smits, 2009;Bernhard et al, 2010). Onchocerciasis is a leading cause of visual impairment and blindness in many developing countries.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Numerous publications call for the integration of control measures that target malaria and neglected tropical diseases (NTDs) with the same platform. [4][5][6][7][8][9] The NTDs are a diverse group of infectious diseases including STH infections, lymphatic filariasis (LF), schistosomiasis, onchocerciasis, and at least 13 others, prioritized by the World Health Organization as such, because they promote poverty and have a negative impact on pregnancy, child health and development, and adult worker productivity. Examples of synergism between malaria and NTD control programs include a reduction in LF transmission by the large-scale rollout of long-lasting insecticide-treated nets (LLINs) and indoor residual spraying (IRS) with insecticides for malaria control 10,11 and the distribution of LLINs and sulfadoxine-pyrimethamine for intermittent preventive therapy for pregnant women by Community-Directed Treatment (CDT) platforms that have been mobilized by the African Program for Onchocerciasis Control (APOC) 12,13 and the Global Program to Eliminate Lymphatic Filariasis (GPELF) 14 in Africa.…”
mentioning
confidence: 99%